Reduction in Depressive Symptoms in Patients with Breast Cancer Following Cognitive Behavioral Psychotherapy Intervention - Ayunda, Bela Sukma; Sofiya, Sofiya; Sunli, M Iqbal; Palupi, Arini Retno (The Avicenna Medical Journal, 2024)
Background: Breast cancer, a malignancy in breast tissue has the highest prevalence among women globally. Around 50% breast cancer patients have experienced depression caused by the illness and its treatments, which is alarming due to its effects on the treatment effectiveness and recovery. This study is performed to know the effects of cognitive behavioral therapy in decreasing depressive symptoms in breast cancer patients.Methods:  The researchers followed a structured and systematic approach sourced from seven databases: ScienceDirect, ResearchGate, PubMed, Google Scholar, Biomed Central, Taylor & Francis Online, and Pharmacophore. The keywords used in this study were “Breast cancer” AND “Cognitive Behavioral Therapy” AND “Depression”. The initial search yielded 1.190 journals. After applying the inclusion and exclusion criteria, 11 journals were found that met criteria. The search was limited to randomized controlled trials, assessed using the JBI critical appraisal for risk of bias.Results: The result shows positive outcomes in breast cancer patients with depression comorbidity following the implementation of cognitive behavioral therapy intervention. These positive changes include enhanced problem-solving skills in relation to psychosocial and emotional aspects, improved adaptability to various situations, and decreasing depressive symptoms.Conclusion: Cognitive behavioral therapy is effective in decreasing depressive symptoms in breast cancer patients